Bioethics in a Latin American Key: Contributions of Unesco's Universal Declaration on Bioethics and Human Rights - Siverino Bavio, Paula (2009)
The author of this article presents a proposal for human rights bioethics and, at the same time, to analyse UNESCO's Universal Declaration on Bioethics and Human Rights from a Latin American perspective. To do so, she begins with a brief historical and conceptual review of bioethics, highlighting the predominance of the principled approach based on four pillars: autonomy, beneficence, non-maleficence and justice. Later on, the author reflects on the criticisms that this approach has received from other perspectives, mainly from Latin American bioethics, which questions its universality and its aptitude to solve the ethical problems of the region. After the above, it is stressed that the Universal Declaration on Bioethics and Human Rights represents significant progress in the defence of human rights in the field of bioethics. Finally, the contributions of the aforementioned Declaration to the advancement of bioethics in a Latin American context are highlighted.